Dynamics of Firm’s Capital Structure Along The Life Cycle of Indonesian Manufacturing Firms - Erika Putri Cempakasari; Muhammad Firdaus; Arief Tri Hardiyanto (School of Business, IPB University (SB-IPB), 2019)
Life cycle of the firm has an important role in the dynamics of firm’s capital structure. A firm will take different funding decision along the life cycle because the firm’s characteristics that affect the capital structure will adjust itself as the tranformation of the life cycle occuring. The research objectives were to analize the dynamic of firm’s capital structure across three-life cycle stages of Indonesian manufacturing companies listed with a total sample of 121 companies observed during the period from 2011 to 2016. By using dynamic panel data analysis with Generalized Method of Moments (GMM) model, we find that profitability and liquidity affect the firm’s life cycle for a growing stage, meanwhile the fixed asset, growth opportunities, profitability, and liquidity affect the capital structure for a mature stage, whereas only liquidity that affects capital structure for a decline stage. The coefficient of lag dependent variable of GMM model representing the previous year capital structure showed an adjustment rate of capital structure. The lowest speed of adjustment occurred on the decline stage which was orderly followed by the growth and mature stage.Keywords: capital structure, life cycle of firm, firm’s characteristics, dynamic panel data analysis